Analisis Pancasila sebagai Ideologi Negara di Era Globalisasi - Marzuki Marzuki; Luthifa Rafifah Rinaldi Putri; Salwa Mazaya Siregar; Muhammad Rapli Harahap (Universitas Maritim AMNI Semarang, 2025)
Pancasila is the basic value of the Indonesian nation, and is the foundation of national and state life in Indonesia since independence. Considering the importance of the existence of Pancasila in Indonesia, of course the creation of the Pancasila ideology has gone through a very long process. This article will highlight and examine the history of the creation of Pancasila and its position as the ideology and foundation of the state. This article will also highlight the position of Pancasila in the era of globalization and how the ideology and foundation of the state are applied in facing the challenges of change in the era of globalization.